2014
DOI: 10.5581/1516-8484.20140028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of βS-globin haplotypes hydroxyurea on tumor necrosis factor-alpha levels in sickle cell anemia

Abstract: BackgroundSickle cell anemia is a chronic inflammatory disease characterized by an increased production of proinflammatory cytokines including tumor necrosis factor-alpha. Hydroxyurea, by decreasing the polymerization of hemoglobin, reduces inflammatory states. The effect of the genetic polymorphisms of sickle cell patients on tumor necrosis factor-alpha levels remains unknown.ObjectiveThe aim of this study was to investigate the association of tumor necrosis factor-alpha levels with β-globin haplotypes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…HU therapy was also observed to significantly reduce HbS levels, which is consistent with results by Shome et al who also found an association between HU use and significantly reduced HbS levels in SCA patients [ 38 ]. We also detected significantly higher HbF levels in SCA-HU + patients compared to controls, which confirms results in previous studies regarding the efficacy of HU in inducing HbF synthesis [ 3 , 34 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HU therapy was also observed to significantly reduce HbS levels, which is consistent with results by Shome et al who also found an association between HU use and significantly reduced HbS levels in SCA patients [ 38 ]. We also detected significantly higher HbF levels in SCA-HU + patients compared to controls, which confirms results in previous studies regarding the efficacy of HU in inducing HbF synthesis [ 3 , 34 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…HU therapy was found to be associated with higher values of MCH and MCV, similar to what was shown by Pallis et al [ 34 ]. On the contrary, Laurentino et al did not observe significant differences in MCH and MCV levels among SCA-HU + and SCA-HU − patients [ 3 ]. The present study found an association between HU therapy and significant reductions in leukocyte, eosinophil, and monocyte counts, confirming its cytoreductive effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effect of HU treatment on plasma TNF-α level yielded controversial results [38,39]. In this study, HU treated patients had a high level of TNF-α.…”
Section: Discussionmentioning
confidence: 83%
“…This important finding supports the association between pro-inflammatory cytokine release and the clinical severity of SCA as these cytokines induce adhesion molecule activity in the endothelium 18 . Moreover, Laurentino et al found higher TNF-α levels in individuals with the Bantu haplotype than those with the Benin haplotype 13 . These data not only reflect the severity of the diseases but also the effect of haplotypes in modulating the SCA phenotype.…”
mentioning
confidence: 53%